“Right Turn” in Israeli Political Life (1965—1977) - V. M. Morozov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The issues related to the events that took place in Israeli political life in the 60s and 70s of the XX century, which went down in history under the name of the “right turn”, when the leftwing parties came to replace the leading left-wing parties since 1949 are examined in the article. It is shown how, with their coming to power, foreign and domestic political approaches have changed, within which the ideas of Zionism-revisionism began to come to the fore. The authors analyze the reasons for the end of the era of the leadership of the left parties in Israeli politics, the essence the “right turn” and its consequences. Particular attention is paid to the activities of such forces of as MAPAI and Likud, which have largely shaped the political landscape of the state since the second half of the 1960s. It is emphasized that this issue is relevant from the point of view of analyzing later events and, in particular, the 2019—2020 crisis during the formation of the Israeli government, as well as intensifying its policy in the Palestinian direction. It has been proved that some of the key factors that still determine the internal political and social atmosphere in the country and the region appeared precisely at the considered historical stage.